2019
DOI: 10.1172/jci66062
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced Krüppel-like factor 9 expression promotes hepatic gluconeogenesis and hyperglycemia

Abstract: Chronic glucocorticoid therapy has serious side effects, including diabetes and fatty liver. However, the molecular mechanisms responsible for steroid-induced diabetes remain largely enigmatic. Here, we show that hepatic Krüppel-like factor 9 (Klf9) gene expression is induced by dexamethasone and fasting. The overexpression of Klf9 in primary hepatocytes strongly stimulated Pgc1a gene expression through direct binding to its promoter, thereby activating the gluconeogenic program. However, Klf9 mutation abolish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 52 publications
6
106
0
1
Order By: Relevance
“…[36][37][38] A recent study showed that glucocorticoids increase the expression of the transcription factor Krϋppel-like factor 9 (KLF9), which in turn augments the expression of PGC1α. 39 Deletion of the KLF9 gene abolished the stimulatory effect of glucocorticoids on glucose output. Hence, GC-induced stimulation of gluconeogenesis involves stimulation of the cascade of KLF9-PGC1α-GRU-containing genes.…”
Section: Glucocorticoid Stimulation Of Gluconeogenesis and The Role Omentioning
confidence: 99%
“…[36][37][38] A recent study showed that glucocorticoids increase the expression of the transcription factor Krϋppel-like factor 9 (KLF9), which in turn augments the expression of PGC1α. 39 Deletion of the KLF9 gene abolished the stimulatory effect of glucocorticoids on glucose output. Hence, GC-induced stimulation of gluconeogenesis involves stimulation of the cascade of KLF9-PGC1α-GRU-containing genes.…”
Section: Glucocorticoid Stimulation Of Gluconeogenesis and The Role Omentioning
confidence: 99%
“…We have found by ATAC-seq that the promoter region of klf9 is one of the most differentially open regions of chromatin in blood cells of adults derived from cortisol-treated embryos, possibly reflecting the chronically elevated cortisol levels maintained by those adults (Hartig et al, submitted). In mice klf9 was recently shown to mediate glucocorticoid-induced metabolic dysregulation in liver 20 . Our RNA-seq results from klf9 -/larvae ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was also shown that hippocampuses of women with major depression were found to overexpress KLF9 19 . Finally, it was recently discovered that Dexamethasone-induced upregulation of Klf9 promotes hepatic gluconeogenesis and hyperglycemia in mice 20 . Thus, klf9 is a GR target gene that dynamically controls GC signaling, and its overexpression is implicated in stress-induced pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the JCI, Cui and colleagues introduce a critical role of the transcription factor Krüppel-like factor 9 (KLF9) in linking GC signaling to gluco neogenesis (8). Through the use of gain-and loss-offunction experiments in hepatocytes and in multiple murine models, they establish that fasting-induced and exogenously administered GCs induce transcription of hepatic Klf9, which then augments Pgc1a and, ultimately, the transcription of gluconeogenic and lipid oxidation genes.…”
Section: Glucocorticoid Control Of Glucose Homeostasis: Missing Linksmentioning
confidence: 99%